Evaluation of DNA and RNA extraction methods. - Chin Han, Edwin Shiaw; Mohd Sidik, Shiran; Cheah, Yoke Kqueen; Tan, Geok Chin; Abdul Rahman, Sabariah (Malaysian Medical Association., 2010)
This study was done to evaluate various DNA and RNA extractions from archival FFPE tissues. A total of 30 FFPE blocks from the years of 2004 to 2006 were assessed with each modified and adapted method. Extraction protocols evaluated include the modified enzymatic extraction method (Method A), Chelex-100 extraction method (Method B), heat-induced retrieval in alkaline solution extraction method (Methods C and D) and one commercial FFPE DNA Extraction kit (Qiagen, Crawley, UK). For RNA extraction, 2 extraction protocols were evaluated including the enzymatic extraction method (Method 1), and Chelex-100 RNA extraction method (Method 2). Results show that the modified enzymatic extraction method (Method A) is an efficient DNA extraction protocol, while for RNA extraction, the enzymatic method (Method 1) and the Chelex-100 RNA extraction method (Method 2) are equally efficient RNA extraction protocols.